Ethical Challenges of Artificial Intelligence Text Generators - Robin Yap; Edward Perry (Adult Education Research Conference, 2022)
AI-text generators thrust academia into an evaluation of the standards of student performance. New technology created new barriers but also potential opportunities to re-evaluate academic excellence. Greater alignment is needed to address our new classroom reality.
Keywords: Artificial intelligence; text generators; ethics